2020
DOI: 10.1369/0022155420927109
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Deleted in Malignant Brain Tumors 1 in Normal Human Tissues

Abstract: Deleted in malignant brain tumors 1 (DMBT1) is part of the innate immune system and is expressed on mucosal surfaces in various tissues throughout the human body. However, to date, the localization of DMBT1 has not been investigated systematically and comprehensively in normal human tissues. In this study, we analyzed the mRNA expression of DMBT1 in human tissue by quantitative real-time PCR and examined its localization and distribution in the tissue by immunohistochemical staining using the monoclonal DMBT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Notably, anti-DMBT1 failed to stain cartilage, but it did stain the same submucosal acini as Siglec-8-Fc (Fig 7, B-F). These data are consistent with the recent report of DMBT1 on human airway submucosal glands and ducts but not respiratory epithelium, 23 as previously reported for Siglec-8 ligands. 9 Likewise, single-cell transcriptomics revealed that DMBT1 gene expression in human lungs and airways is remarkably restricted to submucosal gland cells.…”
Section: Purification and Identification Of The Human Airway Siglec-8supporting
confidence: 93%
See 1 more Smart Citation
“…Notably, anti-DMBT1 failed to stain cartilage, but it did stain the same submucosal acini as Siglec-8-Fc (Fig 7, B-F). These data are consistent with the recent report of DMBT1 on human airway submucosal glands and ducts but not respiratory epithelium, 23 as previously reported for Siglec-8 ligands. 9 Likewise, single-cell transcriptomics revealed that DMBT1 gene expression in human lungs and airways is remarkably restricted to submucosal gland cells.…”
Section: Purification and Identification Of The Human Airway Siglec-8supporting
confidence: 93%
“…In nasal lavage samples, most DMBT1, a multifunctional protein, does not carry the Siglec-8 binding determinant, is likely decorated with other glycans, and supports other functions on the airway surface. 18,19 DMBT1 is expressed on many human tissues, 23 most abundantly on intestine and salivary gland, where it may not carry Siglec-8 ligands (preliminary data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…DMBT1 (Deleted in Malignant Brain Tumors 1) and SCGB3A1 (Secretoglobin Family 3A Member 1) encode small secreted proteins expressed at high levels by mucosal tissues throughout the body [ 39 , 40 , 41 ]. An early microarray study also reported downregulation of SCGB2A1 in pterygium [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigating the distribution and localization of DMBT1 in healthy human tissue found that the DMBT1 cycle threshold (Ct) values in the jejunum and colon were 17 and 22, respectively 36 . In comparison, the Ct values for saline-treated mice were 28 and 20 for the jejunum and colon, respectively.…”
Section: Discussionmentioning
confidence: 99%